Alerters and greetings in small talk among Malay students - Ahmad, Normah; Mamat, Roslina; Ahmad, Amirah; Zubbir, Nadiah (International Journal of Early Childhood Special Education, 2022)
In this study, small talk refers to phatic communication and social talk, which contrasted with core business and work-related talk. Small talk often serves as a “lubricant” that makes subsequent communication go smoothly. This study is a part of a bigger study that examines how small talks are conducted among public university students in Malaysia. This particular study only focuses on alerters and greetings used in small talk. Free Discourse Completion Task (FDCT) approach was used to collect data in this investigation. A total of 54 Malay respondents participated in answering the FDCT. The results indicate that the participants used alerters in all 8 situations. However, Title/Role is used more frequently in situations where the speaker has a lower status than the hearer. In situations where the status is equal, Attention Getters are frequently used. Formal greetings are found in all situations and are used more frequently compared to informal greetings. This study also shows that Malay speakers place a higher value on power status than familiarity when greeting others.